Effects of Monitoring on Mortgage Delinquency: Evidence From a Randomized Field Study. (13th November 2014) - Moulton, Stephanie; Collins, J. Michael; Loibl, Cäzilia; Samek, Anya
Abstract In the wake of the housing crisis in 2008, U.S. policymakers have developed a range of policy proposals to address the risk of mortgage borrowers going into payment default. Some of these proposed regulations would effectively eliminate certain loans with riskier borrower characteristics from the market. Such prescriptive approaches fail to recognize alternatives that permit riskier loans to be made, but require postorigination practices designed to offset elevated default risk by improving the capability of individual borrowers to make timely payments. This study provides evidence of one such approach. Through a randomized field experiment, we test the impact of goal setting and external monitoring on mortgage delinquency. First‐time homebuyers who completed a financial planning module and received quarterly contact from a financial coach are less likely to become delinquent or default on their mortgages. These results suggest that relatively low cost procedures embedded into loan servicing may increase adherence to timely repayments, thereby reducing the probability of delinquency while still permitting riskier borrowers to participate in credit markets.